Convenient synthesis of 5-methylene-4-substituted-2(5H)-furanones - Mahajan, Vishal A.; Shinde, Popat D.; Borate, Hanumant B.; Wakharkar, Radhika D. (Tetrahedron Letters, 2005)
A synthesis of novel 4-(substituted)benzyl-5-methylene-2(5H)-furanones involving Stobbe condensation of substituted aldehydes with ethyl levulinate followed by treatment with acetic anhydride in the presence of sodium acetate, has been developed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: 5-methylene-2(5H)-furanones; acetic anhydride; arylaldehydes; ethyl levulinate; sodium acetate

Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution

Synthesis and evaluation of 4/5-hydroxy-2,3-diaryl(substituted)-cyclopent-2-en-1-ones as cis-restricted analogues of combretastatin A-4 as novel anticancer agents - Gurjar, Mukund K.; Wakharkar, Radhika D.; Singh, Anu T.; Jaggi, Manu; Borate, Hanumant B.; Shinde, Popat D.; Verma, Ritu; Rajendran, Praveen; Dutt, Sarjana; Singh, Gurvinder; Sanna, Vinod K.; Singh, Manoj K.; et al. (Journal of Medicinal Chemistry, 2007)
A new series of 2,3-diaryl-4/5-hydroxy-cyclopent-2-en-1-one analogues replacing the cis double bond of combretastatin A-4 (CA-4) by 4/5-hydroxy cyclopentenone moieties was designed and synthesized. The analogues displayed potent cytotoxic activity (IC50 < 1 mu g/mL) against a panel of human cancer cell lines and endothelial cells. The most potent analogues 11 and 42 belonging to the 5-hydroxy cyclopentenone class were further evaluated for their mechanism of action. Both of the analogues led to cell cycle arrest at G2/M phase and induced apoptosis in endothelial cells. Antitubulin property of 42 was superior to 11 and comparable to CA-4. The compound 42 had better aqueous solubility, metabolic stability, and pharmacokinetic profile than CA-4 and also demonstrated significant tumor regression in the human colon xenograft model. Our data suggests that cis-restricted analogues of CA-4 are a new class of molecules that have the potential to be developed as novel agents for the treatment of cancer.